The satisfaction of government servant on e-Government at selected government agencies in Dungun Terengganu / Nor Aqma Nadira Abu Baker et al. - Abu Baker, Nor Aqma Nadira; Mohmad Rahim, Nor Hakimah; Muzamil, Nurul Aini; Wan Mohd Nasir, Wan Nazirah (2011)
This study was conducted to identify the satisfaction of government servant on e-government at selected government agencies in Dungun, Terengganu. The respondent for this study are staff from departments at the selected government agencies which used e-government. A survey questionnaire was responded by 163 staff to indicate the frequency ease of use and perceive usefulness of e-government. This study was also conducted to identify the satisfaction of government servant towards e-government. The findings showed that most of the types of e-government that frequently use by government servant were Human Resources Management Information System (HRMIS). It was also found that the government servant as a user were satisfied with the e-government services. E-government provide better services with user friendly, time saving, can access information needed any time, easy to understand and also the most important is easy to use. From the findings, it can be concluded that the government servant satisfied with the use of e-government. It also can be concluded that the government servant agree that the use of e-government give lot of benefits to them. E-government was really helpful, have accurate information, reduce paper usage in office and also the use of e-government can increase their job performance.